Pemberdayaan Kelompok Tani Melalui Pendampigan Manajemen Keuangan dan Pembukuan Sederhana dalam Pengelolaan Usaha Tani di Kelurahan Makotyamsa, Distrik Mayamuk, Kabupaten Sorong - Sandi H. Pasaribu; Adi Nugroho; Korina Sauyai; Fanda Djitmau; Nimbrot Slofle (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This Community Service program was carried out in Makotyamsa Village, Mayamuk District, Sorong Regency, aiming to empower a farmer group through mentoring in financial management and simple bookkeeping for farm business operations. The main problem faced by the target farmer group was the absence of separation between personal and farm business finances, minimal recording of production and sales transactions, and the inability of farmers to accurately calculate production costs, revenue, and business profit. This condition made it difficult for farmers to make sound business decisions and hindered their access to financing from financial institutions due to the lack of adequate financial records. The program was implemented through a participatory approach involving socialization, financial literacy training, and mentoring in preparing simple bookkeeping, including a cash book, a production and sales record book, and a simple profit-and-loss calculation for the farm business. The results show an improvement in farmer group members' understanding of the importance of financial recording, increased ability to independently prepare simple bookkeeping, and growing awareness of separating farm business finances from household finances. In addition, this mentoring strengthened the financial administrative order of the farmer group as an economic institution for farmers.